Upgrading and Repairing PCs - Mueller, Scott (Que, 2005)
Suitable for courses at all levels in PC maintenance and repair. This title focuses on several important PC technologies. It also includes a DVD containing more than two hours of digital video demonstrating PC maintenance and repair.
Keywords: Computer Science; Technology; Microcomputers -- Upgrading; Microcomputers -- Maintenance and Repair; Microcomputers -- Equipment and Supplies